Effect of CaCl2 Sprays in Different Fruit Development Stages on Grape Berry Cracking - Shi, Hao; Zhou, Xiangyu; Qin, Mengling; Wang, Wenlong; He, Xiaoe; Zhou, Wenhua (Frontiers in Plant Science, 2022)
Grape cracking is a common phenomenon, causing considerable economic losses to growers. The objective of the present study was to determine whether calcium treatment at different fruit development stages can decrease the incidence of grape berry cracking in the cracking-susceptible Vitis vinifera cultivar ‘Li Xiu’. The results indicated that calcium treatment at flowering period (Ⅱ) can significantly decrease the fruit-cracking rate. There are three reasons for this observation. Firstly, Spraying calcium during flowering period is more conducive to the absorption of calcium by grapes, the increase in calcium content in the peel enhanced the peel mechanical properties, and increased the resistance to fruit-cracking. Second, the calcium treatment decreased the expression level of glucose metabolism related gene, and then decreased the PG and cellulase activities, delayed the degradation of pectin and cellulose, increased the peel protopectin content. Three, the calcium treatment decreased the expression level of ABA related gene, the synthesis of endogenous abscisic acid (ABA) as well as the soluble sugar and total soluble solid contents, which ultimately increased fruit firmness, lowered the osmotic pressure, and peel turgor pressure.